An analytical study of folk musical instruments of the rural area of Tripura - Sarkar, Joyanta (Research Journal in Advanced Humanities, 2023)
A music library or music application's listening and search experiences can be greatly enhanced by music recommendation systems. There is simply too much music available in the market for a user to efficiently navigate tens of millions of songs. The demand for good music recommendations is so great that the field of MRS (Music Recommendation Systems) is growing quickly. Extraction of relevant information from user reviews of instrumental music was the primary motivation behind the development of the rating-based recommendation system. On the passage of times most of instruments are not being used by the new generation people as a result, these musical instruments are being wiped out from the world. The research discusses the main features of the performance of Folk Instrumental Music (FIM). In public concert Tripura conditions, it addresses different components of the FIM conducted. The research also examines the components historically recommended by FIM performers and the results provided by music in performances such as raga mood, tranquilly, scalability and astonishments.